Beach profiling and ghost crab densities on a hawksbill turtle nesting beach in the Seychelles. Issue 4 (2nd October 2021) - Gane, Julie A; Downs, Colleen T; Harris, Benjamin; Brown, Mark
Abstract : Increasing beach sediment loss from erosion and high levels of crab Ocypode spp. predation are threatening turtle nests and nesting habitat. The 900 m long beach on Cousine Island, Seychelles, supports a nesting population of approximately 70–130 hawksbill turtle Eretmochelys imbricata nests each season. Seasonal and storm-related erosion and accretion cycles on Cousine Island have the potential of destroying 50% or more of all turtle egg clutches on the island in a single nesting season. Observed crab predation rates had reached 90–100% in preferred nesting beach zones in previous years. This has resulted in intensive management measures to minimise turtle egg and nest losses. We investigated the distribution and population density of ghost crabs and the morphology of the beach across the different beach area zones and across the turtle-nesting season during 2014–2015. Crab burrow numbers varied between beach zone areas and across the season and were highest on the backshore. Crab density correlated negatively with available beach area, and we found that crab density increased in the presence of turtle nests. When examining beach dynamics, we found them to be cyclical and found the nesting beach prone to higher levels of erosion than accretion with significant changes in beach width throughout the season. The mean vertical beach elevation drop on Cousine Island was higher than what hawksbill turtles have been reported to prefer. We suggest the continuation of beach elevation monitoring and management to use the beach morphology data to assist with hawksbill turtle nest translocations to minimise nest losses and maximise hatchling recruitment success.